The significance of incidental breast findings on routine computed tomography of the chest - Al-Hilli, Mohammed; Mustafa, Abdullateef A.; Abdul Wahid, Hiba M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: with the dramatic increase in the use of chest computed tomography (CT) for diagnostic or screening purposes, incidental breast lesions faced more frequently; while most of these incidental breast findings are benign; nevertheless, breast cancer be existing.Objectives: to determine the imaging characteristic of incidentally detected breast lesions in routine chest computed tomography and to review the outcome of further assessment of these abnormalities.Patients and methods: a prospective study performed on (33 patients) during the period from October 2014 to November 2015 in AL Shaheed Ghazi Al Hariri hospital, Baghdad teaching hospital, and Radiology Institute at Medical city complex, Baghdad. All patients were female and their ages ranging from (18-74) years. Then breast lesions found incidentally at CT scan identified and their CT features analyzed and include number of lesions, size, location, shape, margin characteristics, and density of the lesion and associated calcification. Most of these patients with incidental breast findings were followed up by performing breast ultrasound (US) and/or mammography in oncology teaching hospital (according to their age) and according to breast imaging and reporting data system (BIRADS); BIRAD- IV and V lesions followed by cytopathological examination and final results were recorded.Results: during the study period, a total of 39 incidental breast lesions were identified on chest CT scan among those 33 patients because some patients had multiple lesions. The mean age of patients for malignant lesions was (53±6.1 years) and for benign lesions was (43.21±0.8years). 25.6%, of incidental, breast lesions found to be malignant and 74.4% found to be benign. Malignant incidental breast lesions tend to have an irregular shape, ill-defined margin and have soft tissue attenuation.Conclusion: Although CT scan is not the primary procedure for the breast imaging, but it can show a significant complementary role in the evaluation of the breast with ultrasound and mammography. A careful review of the breast and accurate characterization of incidental breast lesions (IBL) would highlight the radiological reports, it would achieve appropriate management for the patients, and this would improve survival. Although some of the findings of benign and malignant breast lesions on CT scan do overlap to some degree, we can conclude that an irregular shape and ill-defined margin are important features that go with malignant breast lesions.